The prettiest - Young, Brigit (Roaring Brook Press, 2020)
When a list appears online ranking the top fifty prettiest girls in the eighth grade, everything turns upside down. Eve Hoffman, ranked number one, can't ignore how everyone is suddenly talking about her looks. Sophie, the most popular girl in school, feels lower than ever when she's bullied for being ranked number two. Nessa Flores-Brady didn't even make the list, but she doesn't care -- or does she? The three girls ban together to find out who made the list but their journey doesn't lead them where they expect.